2020
DOI: 10.1371/journal.pone.0234549
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in NECTIN4 encoding an adhesion molecule are associated with continued opioid use

Abstract: Methadone is a synthetic opioid used as maintenance treatment for patients addicted to heroin. Skin irritation is one of the adverse events caused by opioid use. 344 methadone maintenance treatment (MMT) patients were recruited with records and measurements on methadone dose, plasma methadone concentrations, and treatment emergent symptom scales (TESS). 15 patients reported with skin irritation. Five SNPs located within the NEC-TIN4 genetic region were genotyped. The NECTIN4 gene within the adherens junction i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…As well as these potential applications in cancer diagnosis, increased levels of soluble Nectin-4 in serum may contribute to the diagnosis and monitoring of asthma ( 62 ) and may also represent a new biomarker for opioid dependence ( 63 , 64 ). To date, most research has focused on Nectin-4 as a transmembrane protein of tumor cells, with less attention paid to soluble Nectin-4.…”
Section: Diagnostic Potential Of Nectin-4mentioning
confidence: 99%
“…As well as these potential applications in cancer diagnosis, increased levels of soluble Nectin-4 in serum may contribute to the diagnosis and monitoring of asthma ( 62 ) and may also represent a new biomarker for opioid dependence ( 63 , 64 ). To date, most research has focused on Nectin-4 as a transmembrane protein of tumor cells, with less attention paid to soluble Nectin-4.…”
Section: Diagnostic Potential Of Nectin-4mentioning
confidence: 99%
“…Both opioid sensitivity and addiction warrant more attention to predict the increased risk of developing maladaptive patterns of opioid use (Table 1; Haufroid & Hantoson, 2015). Other GWAS and candidate gene studies found several other genetic variations possibly associated with phenotypes related to opioid sensitivity or addiction within/around gene regions, such as MCOLN1, PNPLA6, DDX18, PTPRD, MYOM2, SNAP25-AS1, NECTIN4, GRK5, and MYOCD (Table 1; Cheng et al, 2020;Cox et al, 2020;Fang et al, 2020;Nielsen et al, 2008;Wang et al, 2018). However, additional genetic research is needed on these important phenotypes that are of paramount clinical importance.…”
Section: (B) Vulnerability To Opioid Dependence and Addictionmentioning
confidence: 99%
“…There is solid evidence of the role that genetic factors play in the development of addictive disorders [6][7][8]. Recent studies using GWAS (Genome-wide association study) have identified several novel genes that are associated with cocaine and opioid use [9][10][11]. Marees et al, (2020) found 2976 novel candidate genetic loci for substance use traits, and identified genes and tissues through which these loci potentially exert their effects [12].…”
Section: Introductionmentioning
confidence: 99%